Legal Protection of Well Known Brands Against Passing Off By Local Entrepreneurs : Case Study of Passing Off of the French Shepora Brand by Shepora Batik - Muhajir Muhajir; Saifudin Saifudin; Lunaraisah Lunaraisah (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The purpose of this research is to determine the criteria that indicate that the Plaintiff's Shepora is a well-known mark that must be protected and how to prove if there has been a passing off of the Plaintiff's mark (Shepora) by Shepora Batik (defendant). This research is a study of documents related to the Passing off of the French Shepora Brand by Shepora Batik. The research results show that the two marks have similarities in essence, because the Defendant's mark also contains the words Sephora, which is the dominant element in the Plaintiff's mark and is also the Plaintiff's mark which has been registered in several countries in the world. The two brand writings are similar in terms of placement, writing method, and letter elements that make up the word Sephora itself, so they produce exactly the same sound when read. The Plaintiff's Sephora was registered in various countries long before the Defendant's brand was registered in Indonesia. If there are similarities in writing, speech and sound with the Plaintiff's brand, it can be ascertained that the Defendant's intentions are other than wanting to piggyback on and benefit from the popularity of the Sephora brand.